Incoherent short pulse scattering from penetrable geophysical media - Adams, Robert John (Virginia Tech, 1995)
A new model for incoherent short pulse scattering from penetrable geophysical media is developed. The model is obtained by assuming that the surface and volume scattered components of the total scattered waveform only minimally interact. A well-known form is used for the surface scattered component of the backscattered waveform while a new form is derived for the volume scattered component of the total scattered waveform. The new volume scattered waveform model is derived from the scalar equation of transfer. This development illustrates the inherent assumptions of the new model as well as previous models. This leads to a reconciliation of parameter estimates obtained using short pulse scattering models and those obtained using other techniques. In addition, the new model represents a generalization of previous volume scattered waveform models in that it incorporates the effects on the average scattered waveform due to surface roughness and layering in the electromagnetic properties of the scattering medium. Previous models are shown to be slightly incorrect special cases of the new model. Finally, the volume scattered waveform model developed herein is demonstrated to be numerically efficient in general, providing a time savings factor of up to 500 relative to a previous model. The scattered waveform model is subsequently used to analyze scattering data obtained over the Greenland ice sheet by the University of Massachusetts at Amherst's 13.5 GHz Advanced Aircraft Flight Experiment (AAFE) altimeter and NASA's 36 GHz Multimode Aircraft Radar Altimeter (MARA). These altimeters operated simultaneously from the same P-3 aircraft platform in September of 1991 and thus provide a dual frequency look at the scattering properties of the ice sheet. In addition, the large section of the ice sheet from which the scattering data is obtained provides an opportunity to evaluate the radar altimeter's ability to distinguish between the various regions of the ice sheet. The results of this analysis suggest that the altimeter ...